KEPUTUSAN TATA USAHA NEGARA YANG BERPOTENSI MENIMBULKAN AKIBAT HUKUM SEBAGAI OBJEK SENGKETA DI PENGADILAN TATA USAHA NEGARA - Muhammad Amin Putra (Jurnal Hukum Peratun, 2020)
Since the enactment of Law No. 30 of 2014 concerning Government Administration, there have been many dynamics of changes in judicial practice in state administrative courts, especially in relation to the object of dispute. One of them is regarding Decisions with Potential Legal Consequences as regulated in Article 87 of the Government Administration Law. The problems that arise are related to the accountability of officials, and also to the declarative decisions and constitutive decisions that are regulated in Article 54 of the Government Administration Law. In this paper it is found that officials who issue declarative decisions are not necessarily free from administrative responsibility and the validity of their decisions is determined by the validity of constitutive decisions (as decisions that have the potential to have legal consequences) on which the declarative decisions are issued. This paper uses a normative-legal research method, namely using secondary data in the form of primary and secondary sources of law, both applicable laws and related literatures.